2015
DOI: 10.1016/j.apsb.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of traditional Chinese medicine preparation, Chinese materia medica and active compounds on ischemia/reperfusion-induced cerebral microcirculatory disturbances and neuron damage

Abstract: Ischemic stroke and ischemia/reperfusion (I/R) injury induced by thrombolytic therapy are conditions with high mortality and serious long-term physical and cognitive disabilities. They have a major impact on global public health. These disorders are associated with multiple insults to the cerebral microcirculation, including reactive oxygen species (ROS) overproduction, leukocyte adhesion and infiltration, brain blood barrier (BBB) disruption, and capillary hypoperfusion, ultimately resulting in tissue edema, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 102 publications
(141 reference statements)
2
121
0
Order By: Relevance
“…However, less than 10 % of patients with ischemic stroke may benefit from t-PA treatment because of the strict eligibility criteria for its use, including a relatively short therapeutic time window less than 4.5 h [21]. Follow-up care after blood flow restoration is also of great concern because I/R leads to serious brain injury [22,23]. Neuroprotective agents are thus urgently needed along with thrombolytic treatment to protect neurons from Edaravone is an important agent, which was luached in Japan as a therapeutic for ischemic stroke through neuroprotection by free radical scavenging in 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, less than 10 % of patients with ischemic stroke may benefit from t-PA treatment because of the strict eligibility criteria for its use, including a relatively short therapeutic time window less than 4.5 h [21]. Follow-up care after blood flow restoration is also of great concern because I/R leads to serious brain injury [22,23]. Neuroprotective agents are thus urgently needed along with thrombolytic treatment to protect neurons from Edaravone is an important agent, which was luached in Japan as a therapeutic for ischemic stroke through neuroprotection by free radical scavenging in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the prevalent factors in the development cascade of I/R injury from stroke [3,4,11,22,23]. As a NOX inhibitor, apocynin is a widely investigated anti-oxidative and anti-inflammatory agent [26].…”
Section: Discussionmentioning
confidence: 99%
“…Various measures to relieve the inflammatory response can significantly protect the blood-brain barrier and prevent encephaledema and nerve injury. It has been found that as the dominant ingredient of astragalus, formononetin can markedly reduce the expression of iNOS, IL-1β and TNF-α, and decrease the activity of matrix metalloproteinases (MMPs) and the permeability of the bloodbrain barrier, as well as improve nerve function deficit and exert marked neuroprotective effects (36). Our results demonstrated that SIRT1 exerted neuroprotective effect by suppressing the expression of inflammation-related markers in rats with CIRI.…”
Section: Discussionmentioning
confidence: 51%
“…These herb medicines can also downregulate the expression of ROS by inhibiting the activation of NADH/NADPH pathway, which result in the downregulation of vascular injury proteins and cytokines [102]. According to the abovementioned multitarget mechanisms, the principle of promoting blood circulation by removing blood stasis became an important tool in the treatment of diabetic vascular complications.…”
Section: Mechanisms Of Blood Circulation Activating Drugs Used Tomentioning
confidence: 99%